2022
DOI: 10.1155/2022/9925693
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Pulmonary Tuberculosis among Children Who Received Antiretroviral Therapy (ART), Northwest Ethiopia: A Multicenter Historical Cohorts Study 2009–2019

Abstract: The human immune deficiency virus (HIV) is the strongest risk factor for endogenous reactivation of pulmonary tuberculosis (PTB) through target reduction of CD4, T-lymphocytes, and cellular immune function. Almost one-third of deaths among people living with HIV are attributed to tuberculosis. Despite this evidence, in Ethiopia, information is scarce and meager regarding PTB incidence after ART initiated for seropositive children. Methods. Facility-based multicenter historical cohort was conducted among 721 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…This study also revealed that being severely stunted increased the hazard of tuberculosis infection by 2.1 times compared to children who were not stunted. Similar studies have been conducted in hospitals in the northwest, Ethiopia [ 38 ], Tanzania [ 39 ], and Uganda and Zimbabwe hospitals [ 40 ]. It's possible that HIV infection causes increased nutrient malabsorption as a result of metabolic changes, resulting in weight loss and stunting over time and exposing people to opportunistic infections earlier.…”
Section: Discussionsupporting
confidence: 62%
“…This study also revealed that being severely stunted increased the hazard of tuberculosis infection by 2.1 times compared to children who were not stunted. Similar studies have been conducted in hospitals in the northwest, Ethiopia [ 38 ], Tanzania [ 39 ], and Uganda and Zimbabwe hospitals [ 40 ]. It's possible that HIV infection causes increased nutrient malabsorption as a result of metabolic changes, resulting in weight loss and stunting over time and exposing people to opportunistic infections earlier.…”
Section: Discussionsupporting
confidence: 62%
“…Merkel zone is topographically located within 34° 10’N and 37° 40’E and latitude 09° 17’N and 12° 06’N and constituted by seven administrative district woreda with two primary and one-referral hospitals. 16 22 According to the 2019 National Population Projection, this region has an estimated 1.3 million inhabitants, both urban and rural. This state has diverse topographic climates including familiar traditional zones of “kola,” “dega,” and “woman dega.” 16 24 Pawe is one of the seven district woreda in Metekel Zone and more than 75% landmass malarious and is classified as “kola,” which is below 1500 m above sea level.…”
Section: Methodsmentioning
confidence: 99%
“…16 22 According to the 2019 National Population Projection, this region has an estimated 1.3 million inhabitants, both urban and rural. This state has diverse topographic climates including familiar traditional zones of “kola,” “dega,” and “woman dega.” 16 24 Pawe is one of the seven district woreda in Metekel Zone and more than 75% landmass malarious and is classified as “kola,” which is below 1500 m above sea level. This serosurvey was conducted in Pawe woreda; patients come for treatment at Felege Selam Health Center.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations